Reliability and validity of the Chinese version of the sunlight exposure questionnaire - Wang, Xiaoxia; Wang, Qin; Li, Zhe; Chen, Mengjie; Guo, Maoting; Kong, Laixi; Chen, Liyuan; Li, Xiaolong; Li, Junjun; Cao, Qieyan; Luo, Zhenhua; Xiong, Zhenzhen; et al. (Frontiers in Public Health, 2024)
Objective: This study aimed to translate and validate the reliability and validity of the Chinese version of the Philippines Sunlight Exposure Questionnaire. Methods: A total of 392 Chinese individuals aged at least 18, residing in various cities in Sichuan province for at least one year, were recruited. The reliability of the Chinese version of the questionnaire was measured through internal consistency, split-half reliability, and retest reliability, while validity was determined by the content validity index and structure validity index. Results: The Chinese version of the Sunlight Exposure Questionnaire, which includes 19 items covering five factors, demonstrated a McDonald's omega coefficient of 0.788. The split-half reliability of the questionnaire was 0.823, and the retest reliability was 0.940. The content validity index (S-CVI) was 0.932. The five-factor structure, supported by eigenvalues, explained 66.2% of the total variance. Confirmatory factor analysis indicated favorable model fit results: χ2/df = 1.852, GFI = 0.938, NFI = 0.922, IFI = 0.962, CFI = 0.962, TLI = 0.952, RMSEA = 0.047. The indicators of the model's fit were within reasonable bounds. Conclusion: The Chinese version of the Sunlight Exposure Questionnaire shows validity and good reliability for assessing sun exposure among adults in a Chinese cultural context.